Managing customer relationships in the emerging markets - guanxi as a driver of Chinese customer loyalty - Lee, L.; Tang, Y.; Yip, L.; Sharma, Piyush (Elsevier, 2017)
Guanxi, a social exchange mechanism built on mutual favors, is an integral part of Chinese culture and a necessary relationship management tool for businesses operating in the People's Republic of China (PRC). This paper uses the cognition-affect-conation trajectory to illustrate the subtle differences between guanxi approach and the conventional relationship marketing approaches on customer loyalty and word-of-mouth intentions. This process is mediated by calculative trust and affective attitude toward the service provider, while operationalizing the in-group identification construct to gauge in-group membership. Findings from a field-survey with Chinese retail-banking customers (N = 420) support most of the hypotheses. Besides extending relationship marketing literature by highlighting the need to incorporate unique aspects of different cultures (especially in the emerging markets), this paper also provides many useful managerial implications and directions for future research on phenomena similar to guanxi (e.g., "blat" in Russia, "wa" in Japan and "inhwa" in Korea).